2000
DOI: 10.2134/agronj2000.9261081x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mulching on Biomass, Nutrients, and Soil Water in Banana Inoculated with Nematodes

Abstract: trient availability, (ii) increased porosity/ improved infiltration, (iii) increased surface rooting. Alternatively, The objective of this study was to determine whether mulching increased surface rooting could have a negative impact mitigated the impact of nematodes on banana (Musa AAA) inocuif nematodes reside primarily in the upper layers of the lated with Radopholus similis (Cobb) Thorne and Helicotylenchus multicinctus (Cobb) Golden. The study was conducted at Interna-soil profile, that is, a larger perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…Obiefuna (1991) found that mulch of crop residues was effective at decreasing nematode populations in plantain. Mulching is reputed also to mitigate the impact of nematodes on banana (Sikora et al, 1989;Kashaija et al, 1999), especially when applied to low fertility systems (McIntyre et al, 2000). The beneficial effects of mulching in plantain and banana have been attributed to improvements in soil physical, chemical and biological properties (Swennen, 1990;Salau et al, 1992;McIntyre et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obiefuna (1991) found that mulch of crop residues was effective at decreasing nematode populations in plantain. Mulching is reputed also to mitigate the impact of nematodes on banana (Sikora et al, 1989;Kashaija et al, 1999), especially when applied to low fertility systems (McIntyre et al, 2000). The beneficial effects of mulching in plantain and banana have been attributed to improvements in soil physical, chemical and biological properties (Swennen, 1990;Salau et al, 1992;McIntyre et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that may influence nematode population densities and the extent of nematode damage to banana roots is crop management such as mulching, a common banana management practice in Uganda (Bananuka and Rubaihayo, 1994). Nematode-related yield losses in East African highland bananas ranging from 15 to 50% have been observed for mixed populations of R. similis and H. multicinctus Speijer and Kajumba, 2000;McIntyre et al, 2000). Data on yield loss caused by P. goodeyi are not available.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of field and laboratory studies have shown that organic mulching can increase soil water storage by reducing storm runoff (Moreno-Ramón et al, 2014;Sadeghi et al, 2015), increasing infiltration (Montenegro et al, 2013), and decreasing evaporation (McIntyre et al, 2000;Sas-Paszt et al, 2014). Chakraborty et al (2010) found that organic mulches had better soil water status and improved plant canopy in terms of biomass, root growth, leaf area index, and grain yield, which subsequently resulted in higher water and nitrogen uptake and their use efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…can affect soil water retention in banana plantations (Mc INTYRE et al, 2000). Furthermore, the benefits of organic matter are known and its application is recommended for banana plantations (SILVA and BORGES, 2008;SOUZA et al, 1999).…”
Section: Previous Research Recommended Microsprinkler Irrigation For mentioning
confidence: 99%